Heterospecific amplexus between Triprion petasatus (Anura: Hylidae) and Incilius valliceps (Anura: Bufonidae) from Yucatán, Mexico - Carbajal-Márquez, Rubén Alonso; Ramírez-Valverde, Tania; Quintero-Díaz, Gustavo Ernesto; García-Balderas, Christian M.; Cedeño-Vázquez, J. Rogelio (Instituto de Ecología, A.C., 2018)
The heterospecific amplex between Triprion petasatus and Incilius valliceps is documented for the first time in the locality of Piste, Yucatan Mexico. This behavior has been documented previously in other amphibians, many of them also explosive reproducers that take advantage of temporary bodies of water, in places with a marked dry season.